Laro Ng Lahi Through the Lens of Junior High School Students: A Phenomenological Inquiry - Myra F. Ruin; Victoria E. Tamban; Marcial M. Bandoy (Humanities, Society, and Community, 2024)
Junior high school students’ knowledge, attitudes, and perceptions of traditional games are crucial to explore, and their integration into curriculum programs can optimize learning and developmental outcomes.  This study aimed to understand and explore the lived experiences of junior high school students regarding their attitude and engagement toward Laro ng Lahi and its cultural significance. Laro ng Lahi has become unfamiliar or is no longer recognized by today’s generation. The researcher aimed to emphasize the love for traditional games.  Traditional games, such as Luksong baka, jump over the person (baka) or "cow," without touching, Patintero where goal for offensive players without being tagged, Piko which hop from section to section without touching the lines and Tumbang preso, tossing a slipper at a can object of the game. This study used a qualitative transcendental phenomenological approach. We aimed to examine the lived experiences of 20 junior high school students. The findings revealed that the students initially found the traditional games to be fun, exciting, and deeply memorable, often evoking strong emotions and a sense of nostalgia. We also identified challenges such as varying levels of student engagement and the need for more inclusive strategies to effectively integrate Laro ng Lahi into the broader educational framework. Our study strongly advocated for a more nuanced approach to incorporating Laro ng Lahi into the curriculum, stressing the need to overcome barriers and leverage these games as a valuable resource for holistic education.